Hydrotherapy in nervous system diseases - Joanna Iłżecka (Kazimierz Wielki University, 2019)
SUMMARY Hydrotherapy is one method used in the rehabilitation treatment of various diseases, including diseases of the nervous system with a positive result. It is used in many exercise programs. It has been shown that hydrotherapy reduces the clinical symptoms of the nervous system diseases, reduces pain and improves quality of life. The mechanism of action of hydrotherapy is omnidirectional; among other things, it has a positive effect on segmental spinal mechanisms, induces muscle relaxation, affects the activity of the autonomic nervous system. The aim of the work was a review of the literature on hydrotherapy in nervous system diseases.